Gallic Acid Impedes Non-Small Cell Lung Cancer Progression via Suppression of EGFR-Dependent CARM1-PELP1 Complex - Wang D; Bao B (Dove Medical Press, 2020)
Dong Wang,1 Burenbatu Bao2 1Department of Oncology of Mongolian-Western Medicine, Affiliated Hospital of Inner Mongolia University for Nationalities, Tongliao 028007, People’s Republic of China; 2Department of Mongolian Medicine Hematology & Oncology, Affiliated Hospital of Inner Mongolia University for Nationalities, Tongliao 028007, People’s Republic of ChinaCorrespondence: Burenbatu BaoDepartment of Mongolian Medicine Hematology & Oncology, Affiliated Hospital of Inner Mongolia University for Nationalities, No. 1742, Huolinhe Street, Horqin District, Tongliao 028007, Inner Mongolia, People’s Republic of ChinaTel/Fax +86-475-8215816Email wangdong7776@126.comBackground: Non-small cell lung cancer (NSCLC) is a common cause of cancer-related deaths. This study identified the regulatory pattern of gallic acid in NSCLC.Methods: Human NSCLC cells were treated with different doses of gallic acid, after which, MTT assay and flow cytometry were performed to determine the survival and apoptotic rate of human NSCLC cells. Then, co-immunoprecipitation assay was performed to analyze the relationships between gallic acid, epidermal growth factor receptor (EGFR), and CARM1-PELP1. Next, we analyzed whether PELP1, CARM1 and EGFR were associated with the effects of gallic acid on NSCLC cells by conducting rescue experiments. The expression pattern of phosphorylated EGFR, EGFR, Ki67, as well as Fas, FasL and Caspase 3 proteins in cancer cells or xenografts was measured by Western blot analysis. Lastly, the role of gallic acid in the tumor growth was assessed in nude mice.Results: The ideal dose of gallic acid that presented good suppressive effect on NSCLC cells were 30 μM, 50 μM and 75 μM, respectively. Gallic acid played an inhibiting role in the activation of EGFR, which further reduced the formation of CARM1-PELP1 complex, ultimately repressed the proliferation and elevated apoptosis of NSCLC cells. Meanwhile, CARM1 repression led to decreased growth, proliferation and migration abilities of NSCLC cells. Animal experiments confirmed that gallic acid contributed to the inhibition of tumor growth in vivo.Conclusion: To sum up, gallic acid could potentially prevent NSCLC progression via inhibition of EGFR activation and impairment of the binding of CARM1 to PELP1, highlighting a novel therapy to dampen NSCLC progression.Keywords: gallic acid, EGFR, CARM1, PELP1, non-small cell lung cancer, CARM1-PELP1 complex